Finding the music - Torres, Jennifer, 1980- (Children's Book Press, an imprint of Lee & Low Books Inc., 2015)
"A young Latina girl accidentally breaks her grandfather's vihuela and searches for someone in the community to fix the instrument, which leads her to discover her grandfather's legacy as a mariachi. Includes an author's note and glossary"--